2019
DOI: 10.1002/adma.201904209
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Bioprinting of Complex Living‐Tissue Constructs within Seconds

Abstract: Biofabrication technologies, including stereolithography and extrusion‐based printing, are revolutionizing the creation of complex engineered tissues. The current paradigm in bioprinting relies on the additive layer‐by‐layer deposition and assembly of repetitive building blocks, typically cell‐laden hydrogel fibers or voxels, single cells, or cellular aggregates. The scalability of these additive manufacturing technologies is limited by their printing velocity, as lengthy biofabrication processes impair cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
452
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 381 publications
(455 citation statements)
references
References 50 publications
1
452
0
2
Order By: Relevance
“…In this study, we demonstrated that the visible light‐initiated photoredox platform not only allows formation of sophisticated, ordered, and graduated constructs but also supported encapsulation of cells at high densities with long‐term survival and function following biofabrication. We believe that this system holds great potential for complex and free‐form architectures that can be obtained through further development of this photoresponsive silk bioink, especially using light‐based biofabrication technologies such as projection lithography, or even via recently developed fast tomographic volumetric bioprinting technologies . Finally, future studies will explore in vivo responses to this new hydrogel system and in particular investigate the beta‐sheet transformation and degradation mechanisms of this new class of silk hydrogel post‐implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that the visible light‐initiated photoredox platform not only allows formation of sophisticated, ordered, and graduated constructs but also supported encapsulation of cells at high densities with long‐term survival and function following biofabrication. We believe that this system holds great potential for complex and free‐form architectures that can be obtained through further development of this photoresponsive silk bioink, especially using light‐based biofabrication technologies such as projection lithography, or even via recently developed fast tomographic volumetric bioprinting technologies . Finally, future studies will explore in vivo responses to this new hydrogel system and in particular investigate the beta‐sheet transformation and degradation mechanisms of this new class of silk hydrogel post‐implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Though such volumetric part generation potentially yields higher throughput (>10 5 mm 3 per hour) 21 than existing DLP and SLA techniques and allows processing more viscous resins (4-93 Pa s) 19,20,22 and even thermoreversible gels 21 , the smallest feature size demonstrated by multi-beam AM is currently limited to approximately 300 µm 18 .…”
mentioning
confidence: 99%
“…Still, regarding in vivo implantation, a significant effort has been put toward improving living 3D modular constructs biointegration into surrounding host tissues by controlling/stimulating angiogenesis with the inclusion of morphogens or mechanical cues . This remains one of the most challenging aspects of bottom‐up tissue engineering but with the advent of sophisticated volumetric light‐based 3D biofabrication‐based approaches for generating flow‐functional multivascular networks, we anticipate that the ex vivo development of functional prevascularized modular tissue constructs will improve in the upcoming years. The scalability and speed of 3D bioprocessing techniques have been recently improved with elegant approaches for rapid printing of anatomically sized living architectures.…”
Section: Discussionmentioning
confidence: 99%
“…E) Tomography‐inspired volumetric bioprinting enables rapid fabrication of large‐scale anatomically shaped constructs in shear‐stress‐free conditions, combining unprecedented printing speed with high cell viability. Reproduced with permission . Copyright 2019, The Authors, published by Wiley‐VCH.…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%
See 1 more Smart Citation